A solvent based separation method for phenolic compounds from low-temperature coal tar. (20th June 2019) - Gai, Hengjun; Qiao, Lin; Zhong, Caiyun; Zhang, Xiaowei; Xiao, Meng; Song, Hongbing
Abstract: Phenolic compounds are mainly derived from coal tar and coal liquefaction oil. The traditional acid-base separation method, also called caustic washing can result in serious environmental problems. In this work, we used ethanolamine (C2 H7 NO) to separate phenolic compounds from coal tar rather than caustic washing. Although a slightly lower efficacy of separation was obtained with C2 H7 NO, extracting phenolic compounds with C2 H7 NO provided better economic benefits than with caustic washing. The factors influencing the separation effect were studied in detail. In addition, the extraction mechanism of ethanolamine method was investigated by analyzing the chemical interaction of C2 H7 NO and phenolic compounds using Fourier transform infrared and nuclear magnetic resonance spectroscopy. Results showed that the phenolic compounds and C2 H7 NO formed complexes through hydrogen bonding, (coordination), leading to the formation of C2 H7 NO complexes, which resulted in the effective separation of phenolic compounds from other components in coal tar. The results are further supported by quantum chemical calculations. Most importantly, the experiment confirmed that the C2 H7 NO in the complex can be recovered via distillation and a complete phenol extraction process was conceptually designed and proposed by simulation. Considering the environmental and economic advantages, the ethanolamine method can be used to reduce the alkali residue and phenol-containing wastewater in the industrial production process, which is beneficial for environmental protection. By calculating the total cost of the two methods, the profit from using the ethanolamine method can reach $173, 000 or more than the caustic washing method. Thus, the proposed ethanolamine method can be used as an environment-friendly substitute for industrial phenol separation. Graphical abstract: Image 1